A new species of the subgenus Tachycines (Tachycines) (Othoptera: Rhaphidophoridae) from Guizhou, China - Huang, Shihui; Luo, Changqing (Zootaxa, 2019)
Adelung (1902) erected the genus Tachycines with Tachycines asynamorus as the type species. In this paper, a new species of the genus Tachycines, subgenus Tachycines, namely Tachycines (Tachycines) huaxi sp. nov., from Guizhou, China is described. This new species is similar to Tachycines (Tachycines) asynamorus. The morphological differentiation between the two species is discussed.